Strategi Guru dalam Mengembangkan Kemampuan Membaca Lancar Level 3 di Kelas Rendah - Mita Riwanda; Chandra Chandra; Salmaini Syafitri Syam (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to identify and describe the most effective teaching strategies in improving level 3 fluent reading skills in lower grade elementary school students. Level 3 fluent reading skills include the ability to read at an appropriate speed, expressive intonation, and good comprehension of reading content. Through a descriptive qualitative approach, this study explores and analyzes various learning techniques that have been proven to support the improvement of reading fluency in early childhood. The research findings reveal that the application of explicit teaching methods, repetition in reading exercises, the use of paired reading techniques, the use of reading texts with levels of difficulty, and active involvement from parents, can synergistically encourage the development of students' reading skills significantly. This study provides important contributions both theoretically and practically, especially for educators, in designing systematic, comprehensive, and sustainable reading learning programs to improve students' literacy competencies from an early age.